# Which of the following are APs ? If they form an AP, find the common difference d andwrite three more terms.(i) (ii) (iii) (iv) (v) (vi) (vii)(viii)(ix) 1, 3, 9, 27,…(x) (xi) (xii)(xiii)(xiv) (xv) 12, 52, 72, 73.....

For a sequence to be an AP, the difference between two consecutive terms remains the same, that is called the common difference of AP

(i) if ak+1 – ak is same for different values of k then the series is an AP.

We have, a1 = 2, a2 = 4, a3 = 8 and a4 = 16

a4 – a3 = 16 – 8 = 8

a3 – a= 8 – 4 = 4

a2 – a1= 4 – 2 = 2

Here, ak+1 – ak is not same for all values of k.

Hence, the given series is not an AP.

(ii) As per the question:

a1 = 2,

a2 = 5/2,

a3 = 3

And

a4 = 7/2

a4 – a3 = – 3= 1/2

a3 – a2 = 3 – = 1/2

a2 – a1 = – 2 = 1/2

Now, we can observe that ak+1 – ak is same for all values of k.

Hence, it is an AP.

And, the common difference = 1/2

Next three terms of this series are:

a5 = a + 4d

= 2 + 4* 1/2

= 4

a6 = a + 5d

= 2 + 5 * 1/2

=

a7 = a + 6d

= 2 + 6 * 1/2

= 5

Hence,

The next three terms of the AP are: 4, 9/2 and 5

(iii) a4 – a3 = - 7.2 + 5.2 = - 2

a3 – a2 = - 5.2 + 3.2 = - 2

a2 – a1 = - 3.2 + 1.2 = - 2

In this, ak+1 – ak is same for all values of k.

Hence, the given series is an AP.

Common difference = - 2

Next three terms of the series are:

a5 = a + 4d

= -1.2 + 4 × (-2)

= -1.2 - 8 = -9.2

a6 = a + 5d

= -1.2 + 5 × (-2)

= -1.2 - 10 = -11.2

a7 = a + 6d

= -1.2 + 6 × (-2)

= -1.2 - 12 = -13.2

Next three terms of AP are: - 9.2, - 11.2 and – 13.2

(iv)a4 – a3 = 2 + 2 = 4

a3 – a2 = - 2 + 6 = 4

a2 – a1 = - 6 + 10 = 4

Here, ak+1 – ak is same for all values of k

Hence, the given series is an AP.

Common difference = 4

Next three terms of the AP are:

a5 = a + 4d

= -10 + 4 × 4

= -10 + 16 = 6

a6 = a + 5d

= -10 + 5 × 4

= -10 + 20 = 10

a7 = a + 6d

= -10 + 6 × 4

= -10 + 24 = 14

Next three terms of AP are: 6, 10 and 14.

(v) a4 – a3 = 3 + 3√2 – 3 - 2√2 = √2

a3 – a2 = 3 + 2√2 – 3 - √2 = √2

a2 – a1 = 3 + √2 – 3 = √2

Here, ak+1 – ak is same for all values of k

Hence, the given series is an AP.

Common difference = √2

Next three terms of the AP are

a6 = a + 5d = 3 + 5√2

a7 = a + 6d = 3 + 6√2

Next three terms of AP are: 3 + 4√2, 3 + 5√2 and 3 + 6√2

(v)

a4 – a3 = 0.2222 – 0.222 = 0.0002

a3 – a2 = 0.222 – 0.22 = 0.002

a2 – a1 = 0.22 – 0.2 = 0.02

Here, ak+1 – ak is not same for all values of k

Hence, the given series is not an AP.

(vii) Here; a4 – a3 = - 12 + 8 = - 4

a3 – a2 = - 8 + 4 = - 4

a2 – a1 = - 4 – 0 = - 4

Since ak+1 – ak is same for all values of k.

Hence, this is an AP.

The next three terms can be calculated as follows:

a5 = a + 4d = 0 + 4(- 4) = - 16

a6 = a + 5d = 0 + 5(- 4) = - 20

a7 = a + 6d = 0 + 6(- 4) = - 24

Thus, next three terms are; - 16, - 20 and – 24

(viii) Here, it is clear that d = 0

Since ak+1 – ak is same for all values of k.

Hence, it is an AP.

The next three terms will be same, i.e. – 1/2

(ix) a4 – a3 = 27 – 9 = 18

a3 – a2 = 9 – 3 = 6

a2 – a1 = 3 – 1 = 2

Since ak+1 – ak is not same for all values of k.

Hence, it is not an AP.

(x) a4 – a3 = 4a – 3a = a

a3 – a2 = 3a – 2a = a

a2 – a1 = 2a – a = a

Since ak+1 – ak is same for all values of k.

Hence, it is an AP.

Next three terms are:

a5 = a + 4d = a + 4a = 5a

a6 = a + 5d = a + 5a = 6a

a7 = a + 6d = a + 6a = 7a

Next three terms are; 5a, 6a and 7a.

(xi) Here, the exponent is increasing in each subsequent term.

a4 = a4, a3 = a3, a2 = a2, a1 = a

a- a3 = a4 - a3

a3 - a2 = a3 - a2

since, the difference is not same,

Since ak+1 – ak is not same for all values of k.

Hence, it is not an AP.

(xii) Different terms of this AP can also be written as follows:

√2, 2√2, 3√2, 4√2, ………..

a4 – a3 = 4√2 - 3√2 = √2

a3 – a2 = 3√2 - 2√2 = √2

a2 – a1 = 2√2 - √2 = √2

Since ak+1 – ak is same for all values of k.

Hence, it is an AP.

Next three terms can be calculated as follows:

a5 = a + 4d = √2 + 4√2 = 5√2

a6 = a + 5d = √2 + 5√2 = 6√2

a7 = a + 6d = √2 + 6√2 = 7√2

Next three terms are; 5√2, 6√2 and 7√2

(xiii) a4 – a3 = √12 - √9 = 2√3 – 3                ( √12 =√ 2 x 2 x 3 = 2√3)

a3 – a2 = √9 - √6 = 3 - √6

a2 – a1 = √6 - √3

Since ak+1 – ak is not same for all values of k.

Hence, it is not an AP

(xiv) The given terms can be written as follows:

1, 9, 25, 49, …

Here, a4 – a3 = 49 – 25 = 24

a3 – a2 = 25 – 9 = 16

a2 – a1 = 9 – 1 = 8

Since ak+1 – ak is not same for all values of k.

Hence, it is not an AP.

(xv) 12, 52, 72, 73.....

a = 1

d = 52 - 1 = 25 - 1 = 24

d = 72 - 52 = 49 - 25 = 24

d = 74 - 49 = 24

As, common difference is same. The sequence is in A.P.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Arithmetic Progression34 mins
Champ Quiz | Arithmetic Progression30 mins
Smart Revision | Arithmetic Progression47 mins
Quiz | Arithmetic Progression44 mins
Smart Revision | General Term of an A.P44 mins
NCERT | Fundamental Theorem Of Arithmetic45 mins
Quiz on Arithmetic Progression Quiz32 mins
NCERT | Arithmetic Progression36 mins
Lets Check Your Knowledge in A.P.49 mins
Get to Know About Geometric Progression41 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses